The PPARγ Agonist Pioglitazone Fails to Alter the Abuse Potential of Heroin, But Does Reduce Heroin Craving and Anxiety. Issue 5 (20th October 2018) - Jones, Jermaine D.; Bisaga, Adam; Metz, Verena E.; Manubay, Jeanne M.; Mogali, Shanthi; Ciccocioppo, Roberto; Madera, Gabriela; Doernberg, Molly; Comer, Sandra D.
ABSTRACT: Possibly through its effects on glia, the peroxisome proliferator-activated gamma receptor (PPARγ) agonist pioglitazone (PIO) has been shown to alter the effects of heroin in preclinical models. Until now, these results have not been assessed in humans. Heroin-dependent participants were randomized to either active (45 mg, n  = 14) or placebo (0 mg, n  = 16) PIO maintenance for the duration of the three-week study. After stabilization on buprenorphine (8 mg), participants began a two-week testing period. On the first to fourth test days, participants could self-administer drug or money by making verbal choices for either option. On the fifth day, active heroin and money were administered and participants could work to receive heroin or money using a progressive ratio choice procedure. Test days 6–10 were identical to test days 1–5 with the exception that, during one of the test weeks, placebo was available on the first four days, and during the other week heroin was available. PIO failed to alter the reinforcing or positive subjective effects of heroin, but it did reduce heroin craving and overall anxiety. Although we were unable to replicate the robust effects found in preclinical models, these data provide an indication of drug effects that deserves further exploration.